A Comparative Study Of Nahdlatul Ulama And Muhammadiyah On E-Commerce Peer-To-Peer Lending - Subkhan, Mohammad; Aziz, Abdul; Wartoyo, Wartoyo; Hardiyanto, Feri (Worldwide Research Publishing, 2023)
Peer-to-Peer Lending has become a significant phenomenon in the development of digital financial services in Indonesia. This comparative study analyzes the perspectives of Nahdlatul Ulama and Muhammadiyah on Peer-to-Peer Lending practices. The aim of this research is to identify the similarities and differences in the views and approaches of these two largest Islamic organizations in Indonesia towards this digital financial service. Comparative study methodology is employed as the approach in this research. Data is obtained through literature analysis, official documents, and interviews with key figures from NU and Muhammadiyah. Analyzed aspects encompass relevant Sharia principles, socio-economic impacts, consumer protection, as well as views on ethics and religious values in the context of Peer-to-Peer Lending services. The results of the analysis show that, overall, the comparative study between Nahdlatul Ulama and Muhammadiyah regarding e-commerce Peer-to-Peer Lending shares common ground. In the perspectives of Nahdlatul Ulama and Muhammadiyah, riba or interest in online lending practices is considered prohibited (haram) as it contradicts Islamic Sharia principles that prohibit ribawi financial transactions. The difference between the two, Nahdlatul Ulama and Muhammadiyah, is predominantly in their legal deduction (istinbath) approach; Nahdlatul Ulama relies on the consensus (Ijma’) of scholars found in classical jurisprudential texts, while Muhammadiyah derives its legal deduction through Bayani Ijtihad, drawing from the textual sources in the Quran and Hadith of Prophet Muhammad. The implications of these findings underscore the need for collaboration between Islamic organizations and Peer-to-Peer Lending industry stakeholders to ensure services aligned with religious values and ethics, as well as to enhance public understanding of the potential risks and benefits of these services. This comparative study provides a deeper understanding of the roles and perspectives of NU and Muhammadiyah on financial technology advancements, offering a more comprehensive view of the social and economic implications of Peer-to-Peer Lending within the context of Indonesian society.